Climate change and desertification syndrome: the interaction of drivers in the drylands of Nigeria and the possibility of reducing adverse changes - Ahmed, Abubakar; Ishak, Mohd Yusoff; Khalil Umar, Nura; Zangina, Aminu Sulaiman; Imam, Muhammad Nasir (Springer, 2024)
This paper presents the linkages of climate change and desertification, sensitivity to desertification, and the combined effects of these environmental hazards on land productivity. The objective of this study is to investigate the multifaceted nature and impact of climate change and desertification in Babura and identify ways to reduce their impact on the environment. This study applied adjusted MEDALUS methodology (Mediterranean desertification and land use) using ten (10) indicators that affected the study area. Remote sensing and GIS were the main techniques used in indices computation and mapping. Erdas imagine 9.2 software was used for the supervised classification to first achieved categorization of image in land use land cover (LULC) thematic features. Shuttle radar topography mission (SRTM) data using spatial analyst tool in ArcMap (extension of ArcGis 10.3) was used to extract digital elevation model and generated from it slope gradient. The ten indicators were integrated into ArcMap and each weighted from 1 to 2 using weighted overlay in ArcMap; thus, the higher the weighting the higher the sensitivity to land degradation. The ten indicators were categorized into climate, soil, and vegetation indicators based on most significant available parameters quantified and assessed on their perceived influence on desertification. The reclassification of climatic indicators, particularly the areas of high rainfall against the areas of low rainfall, assumed higher weighting indicating higher sensitivity to land degradation. Approximately 48.72% of the study area, with Babura being particularly critical, is highly sensitive to desertification, while most of the study area (676.79–5950.44 m2) consists of areas with very low erosion protection quality.